The research of hepatoprotective activity in experimental hepatitis influenced by 1,2,4-triazole derivatives - I. M. Bilay; E. O. Mihayluk; V. V. Parchenko; A. G. Kaplaushenko; A. I. Panasenko; E. G. Knysh (Zaporozhye State Medical University, 2014)
Aim. The search of new high-effective drugs is an actual problem of modern science. The purpose of our research was the pharmacological screening of 1,2,4-triazoles derivatives. Experiments have been performed on adult Wistar white rats. Methods and results. Compounds have been entered in a 1/10 dose of LD50, which have been determined before performing experiments. The article presents hepatoprotective activity of new synthesized compounds in simulated acute liver injury. We present a comparison with reference drugs in the experiment. Сonclusion. Screening has shown that these class of compounds is promising for further research.